Ecological and Genetic Divergences with Gene Flow of Two Sister Species (Leucomeris decora and Nouelia insignis) Driving by Climatic Transition in Southwest China - Zhao, Yujuan; Yin, Genshen; Pan, Yuezhi; Gong, Xun (Frontiers in Plant Science, 2018)
Understanding of the processes of divergence and speciation is a major task for biodiversity researches and may offer clearer insight into mechanisms generating biological diversity. Here, we employ an integrative approach to explore genetic and ecological differentiation of Leucomeris decora and Nouelia insignis distributed allopatrically along the two sides of the biogeographic boundary ‘Tanaka Line’ in Southwest China. We addressed these questions using ten low-copy nuclear genes and nine plastid DNA regions sequenced among individuals sampled from 28 populations across their geographic ranges in China. Phylogenetic, coalescent-based population genetic analyses, approximate Bayesian computation (ABC) framework and ecological niche models (ENMs) were conducted. We identified a closer phylogenetic relationship in maternal lineage of L. decora with N. insignis than that between L. decora and congeneric Leucomeris spectabilis. A deep divergence between the two species was observed and occurred at the boundary between later Pliocene and early Pleistocene. However, the evidence of significant chloroplast DNA gene flow was also detected between the marginal populations of L. decora and N. insignis. Niche models and statistical analyses showed significant ecological differentiation, and two nuclear loci among the ten nuclear genes may be under divergent selection. These integrative results imply that the role of climatic shift from Pliocene to Pleistocene may be the prominent factor for the divergence of L. decora and N. insignis, and population expansion after divergence may have given rise to chloroplast DNA introgression. The divergence was maintained by differential selection despite in the face of gene flow.